THE IMPACT OF GOLD MINE WITHOUT PERMIT ( PETI ) FISHERMEN OF THE ECONOMIC AND SOCIAL VILLAGE SUNGAI ALAH SUBDISTRICT OF HULU KUANTAN DISTRICT KUANTAN SINGINGI PROVINCE RIAU - Mahgfirah '; Eni Yulinda; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on September 2013 in Sungai Alah Village, Hulu Kuantan Sub District, Kuantan Singingi District, Riau province. This study aimed to : To determine the impact of illegal mining operation to number of fishermen, determine illegal mining’s impact to fishermen’s socio economic , determine impact of illegal mining on the type of fish before and after the operation of the illegal miners.This study used survey data collection techniques by used questionnaires to selected respondents where respondents numbered 16 , 6 and 10 was fishermen fishing remains sideline . PETI impact on number of fishermen , fishing gear and fish species was decline , fishermen’s socio economic impact was. Provided social assistance to rural communities and also cause disease . Economic impact : reduced revenue in fisheries, was :Rp. 10.200.000 to Rp. 4.300.000. While the non- fisheries sector was : Rp. 23.000.000 to Rp. 42.000.000.Key words : PETI, Fisherment’s, Social and Economy, Sungai Alah Village.